Exploring the Severity of Dependence Scale (SDS) as a possible measure of nicotine dependence. Issue 2 (2nd April 2016) - Mercincavage, Melissa; Smyth, Joshua M.; Branstetter, Steven A.; Catley, Delwyn
ABSTRACT: Background: The time to first cigarette (TTFC) of the day is an emerging single-item indicator of nicotine dependence due to its robust associations with indices of physical dependence. However, it is unclear if this measure adequately captures other dimensions of dependence. The Severity of Dependence Scale (SDS) is a brief questionnaire used to assess psychological aspects of dependence that has not yet been extensively applied to smoking research. Methods: We examined associations between the SDS and TTFC among 255 smokers during the baseline session of a cessation trial. We also examined associations of the SDS and TTFC with biobehavioral dependence indices, quitting behaviors, and cognitive-affective variables and compared the relative contributions of both measures in predicting these variables. Results: TTFC was unrelated to SDS total score, but was related to individual SDS items. TTFC, but not SDS, was correlated with indices of physical dependence (e.g., cigarettes per day [CPD], carbon monoxide [CO]). Both TTFC and SDS were associated with quitting behaviors, with opposite directionality of associations. TTFC and SDS were both associated with cognitive-affective variables, but SDS outperformed TTFC in strength and number of these relationships. Including both the SDS and TTFC as regression model predictors often increased the amount of variance explained. Conclusions: Findings suggest that SDS and TTFC assess different constructs of nicotine dependence; among smokers, the SDS appears to tap into nonphysical components of dependence (e.g., loss of control) that relate to quitting motivation and affect. Assessing nicotine dependence using only the SDS may fail to capture physical dependence and, further, may not reflect the same domains of addiction the SDS assesses in other drugs of abuse. Nonetheless, using 3 SDS items in addition to TTFC may offer utility over using TTFC alone.